EXCLUSIVE BREASTFEEDING: Indonesian Mothers Awareness in Providing Exclusive Breastfeed - Hastuti, Anita (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
The awareness of a mother in giving milk to her child is the main capital. Because then, he will try as much as possible, in order to produce milk. On the other hand, giving milk is an effort of a mother's love for her child, with the hope that her child can live healthy and grow perfectly. Therefore, awareness of giving exclusive breast milk is important. This research was conducted to look at the various factors that influence a mother's awareness of giving exclusive breastfeeding to her baby. The subjects of this study were mothers who were breastfeeding their babies, aged between 1 month to 12 months, in Kampar district, Indonesia. The research method was carried out using descriptive quantitative and test tests Chi-square. The research sample was carried out in a simple random manner with a total of 50 respondents. The results showed that the sensitivity of a mother in giving exclusive breast milk to her baby was greatly influenced by several fundamental factors, especially knowledge. This is a motivation in itself, how can a mother who has a baby try to do various things so that she can provide breast milk naturally. So that there is hope, his child will grow into a healthy child.